2009
DOI: 10.2105/ajph.2008.150474
|View full text |Cite
|
Sign up to set email alerts
|

Left Too Early: The Effects of Age at Separation From Parents on Chinese Rural Children's Symptoms of Anxiety and Depression

Abstract: China's explosive economic growth appears to exact a significant toll on left-behind children's mental health, particularly on children whose parents left early in their lives. The unintended consequences of the economic boom on child development need to be further examined in prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
140
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(155 citation statements)
references
References 18 publications
14
140
0
1
Order By: Relevance
“…By this hypothesis, Prader-Willi infants and children may essentially undergo a process of self-induced maternal deprivation, whereby their low levels of care solicitation lead to reduced interaction with the mother and dysregulated social-emotional development. The primary line of evidence supporting this hypothesis, in addition to the theory and data described above, is that maternal deprivation, due to diverse causes including reduced physical care, temporary early separation or permanent loss, is a well-documented, highlypenetrant causal factor in the etiologies of depression (e. g., Pesonen et al 2007;Tyrka et al 2008;Liu et al 2009), schizophrenia (reviewed in Read and Gumley 2008) and schizotypy (Anglin et al 2008). Convergent evidence for interactions of maternal deprivation with imprinted gene expression comes from a study of mice, where 2 (5.4%) of 37 genes significantly upregulated in the hypothalamic paraventricular nucleus of young mice in response to maternal deprivation were imprinted (Gtl2 and Ipw), a higher proportion than expected given an approximate 1.2% (120 of 10,000) (http://igc.otago.ac.nz/ table.html) of brain-expressed genes imprinted in the mouse genome (χ2 = 5.43, P < 0.05).…”
Section: Prader-willi Syndromementioning
confidence: 95%
“…By this hypothesis, Prader-Willi infants and children may essentially undergo a process of self-induced maternal deprivation, whereby their low levels of care solicitation lead to reduced interaction with the mother and dysregulated social-emotional development. The primary line of evidence supporting this hypothesis, in addition to the theory and data described above, is that maternal deprivation, due to diverse causes including reduced physical care, temporary early separation or permanent loss, is a well-documented, highlypenetrant causal factor in the etiologies of depression (e. g., Pesonen et al 2007;Tyrka et al 2008;Liu et al 2009), schizophrenia (reviewed in Read and Gumley 2008) and schizotypy (Anglin et al 2008). Convergent evidence for interactions of maternal deprivation with imprinted gene expression comes from a study of mice, where 2 (5.4%) of 37 genes significantly upregulated in the hypothalamic paraventricular nucleus of young mice in response to maternal deprivation were imprinted (Gtl2 and Ipw), a higher proportion than expected given an approximate 1.2% (120 of 10,000) (http://igc.otago.ac.nz/ table.html) of brain-expressed genes imprinted in the mouse genome (χ2 = 5.43, P < 0.05).…”
Section: Prader-willi Syndromementioning
confidence: 95%
“…Previous literature has suggested that left-behind children may be at greater risk of depression, anxiety, and loneliness as a result of separation from their parents. 27,28 Compared with children living with both parents, the leftbehind children are also reported to have lower levels of satisfaction with life, including lower levels of happiness and quality of life. 29,30 Study Results…”
Section: On December 18 2016 By Hw Teammentioning
confidence: 99%
“…Moreover, often these studies have collected data only on migrant children or children left behind, failing to sample a comparison group of non-migrant children, thus making it impossible to assess the effect of migration on children's lives (e.g. Li, 2004;Liang, 2004;Women's Federation of Meishan Municipality, 2004;Zhao, 2004;Liu, Li, and Ge, 2009;Wong, Chang, and He, 2009). Many of the studies of children left behind are summarized by Xiang (2007), who points out that in a systematic comparison of left-behind and other children in a middle school in Fujian Province, Huang (2004) found that the emotional health of left-behind children was only marginally worse than that of other children.…”
Section: Introductionmentioning
confidence: 99%